Mainstreaming knowledge management and sharing to support organizational learning and increase the impact of agricultural research for development - Staiger Rivas, Simone; Álvarez, S.; Russell, N. (2013)
Making agriculture more competitive, resilient, and sustainable in developing countries requires continuous sharing of research processes and outcomes between farmers, development experts, scientists, and policymakers, among others. In recent years, new opportunities have emerged for research organizations to adopt innovative practices that foster knowledge management and sharing (referred to subsequently as KM) both internally and within their networks. This policy brief summarizes 10 years of experience with KM in CIAT and CGIAR, with particular emphasis on options for mainstreaming KM in research for development. The document is intended for professionals and management teams interested in a comprehensive KM approach for their organizations and networks.